PERILAKU HIDUP BERSIH DAN SEHAT DITINJAU DARI TINGKAT LITERASI KESEHATAN STUDI DI SDN 02 PENANGGAL - CANDIPURO KABUPATEN LUMAJANG - Anis Sukowati; Nurul Mawaddah; Ika Suhartanti; Eka Diah Kartiningrum (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Health literacy on clean and healthy living behavior in elementary schools is very important to be instilled from an early age to improve the degree of health. This study aims to determine the relationship between health literacy level and clean and healthy living behavior at SDN 02 Penanggal, Candipuro District, Lumajang Regency